2022
DOI: 10.5194/acp-22-3251-2022
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of low-level clouds and precipitation to anthropogenic aerosol emission in southern West Africa: a DACCIWA case study

Abstract: Abstract. During the West African summer monsoon, pollutants emitted in urbanized coastal areas modify cloud cover and precipitation patterns. The Dynamics-Aerosol-Chemistry-Cloud Interactions in West Africa (DACCIWA) field campaign provided numerous aircraft-based and ground-based observations, which are used here to evaluate two experiments made with the coupled WRF–CHIMERE model, integrating both the direct and indirect aerosol effect on meteorology. During one well-documented week (1–7 July 2016), the impa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Using COSMO-ART model in a simulation for 2-3 July 2016 case, Deetz et al (2018) found that under the influence of the Maritime Inflow (MI, cold air) from Guinean Gulf, stratus-stratocumulus transition are susceptible to the aerosol direct effect resulting in a spatial shift in the MI front and a temporal shift of the cloud transition. Over SWA and influenced by anthropogenic emission sources, the breakup time of LLSCs can be delayed by one hour and daily precipitation rate can decrease by 7.5% according to Deroubaix et al (2022). Moreover, semi-direct and indirect effects were studied together by varying respective magnitude or forcing emission of anthropogenic aerosols but they were not examined separately.…”
Section: Introductionmentioning
confidence: 99%
“…Using COSMO-ART model in a simulation for 2-3 July 2016 case, Deetz et al (2018) found that under the influence of the Maritime Inflow (MI, cold air) from Guinean Gulf, stratus-stratocumulus transition are susceptible to the aerosol direct effect resulting in a spatial shift in the MI front and a temporal shift of the cloud transition. Over SWA and influenced by anthropogenic emission sources, the breakup time of LLSCs can be delayed by one hour and daily precipitation rate can decrease by 7.5% according to Deroubaix et al (2022). Moreover, semi-direct and indirect effects were studied together by varying respective magnitude or forcing emission of anthropogenic aerosols but they were not examined separately.…”
Section: Introductionmentioning
confidence: 99%